Comparison of Students’ and Teachers’ Opinions Toward Digital Citizenship Education - Tangül, Hasan; Soykan, Emrah (Frontiers in Psychology, 2021)
The impact of the COVID-19 pandemic has led to the temporary interruption of educational activities in the classroom. Digitalization of the classrooms emerged as a need following that process. The objective of this study is to compare the digital citizenship levels of teacher candidates studying in the last year at the departments of classroom teaching and primary school classroom teachers and to reveal their needs. A total of 38 primary school classroom teachers and 27 classroom teacher candidates in the last year of teaching programs in North Cyprus participated in the research. This descriptive study was designed as a case study, which is a qualitative research approach. The data of the study were gathered within the frame of a grounded theory coding process and were analysed through descriptive analysis, content analysis and the constant comparison technique. The digital citizenship levels of the classroom teachers and teacher candidates were analysed according to the sub-dimensions of digital citizenship. As a result of the research, it was found that the digital citizenship sub-dimension scores of the classroom teachers were higher than the teacher candidates and that the teacher candidates needed digital citizenship education.